Utilization of mangosteen peel extract (Garcinia mangostana) to inhibitor Vibrio Parahaemolyticus bacteria in tiger shrimp (Penaeus monodon) - Salamah, Salamah; Mahdaliana, Mahdaliana; Wahyuni, Riri; Rusydi, Rachmawati; Erlangga, Erlangga (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Windu shrimp (penaeus monodon) is one of the export commodities that are a priority of the Ministry of Marine Affairs and Fisheries (KKP) in 2021-2024, one of the factors that cause disease in windu shrimp cultivation is vibrio parahaemolitycus bacteria. This study aims to determine the use of mangosteen peel extract (Garcinia mangostana) in feed as an inhibitor or Vibrio parahaemolyticus bacteria in windu shrimp (Penaeus monodon). This research was conducted from January to March 2022 at the Hatchery Laboratory and Cultivation Technology program of Malikussaleh University Aquaculture study program. The method used in this study was carried out in an experimental way using a complete random design (RAL) non-factorial with four three-treatment treatments. The results showed that the feeding mixed with mangosteen skin extract with different doses had an effect on clinical symptoms, healing duration, survival and absolute growth. Statistical test analysis with test F showed that feed mixed with mangosteen peel extract (garcinia mangostana) had a very noticeable effect on the duration of healing, survival, absolute growth of windu shrimp (Penaeus monodon) infected with vibrio parahaemolitycus bacteria and organoleptic test on feed. The water quality range is in the good range for the maintenance of windu shrimp.